Plants: A promising tool for soil remediation for environmental sustainability - Olamiriki , Esther Funmi; Shittu, Olubunmi Samuel (Journal of Pure and Applied Agriculture, 2023)
The issue of soil contamination caused by various anthropogenic activities is a global concern. The detrimental effects of these contaminants on the environment cannot be overemphasized in terms of the threat posed to plants and animals. The contaminants affect the soil properties, the crop biomass, and its yield. Moreover, these contaminants contain some toxic heavy metals (HMs) that cannot be decomposed, which accumulate in the ecosystem. Thus, they enter the food chain in the ecosystem. Researchers have widened their research in proffering solutions to the problems posed by soil contamination with possible remediation strategies. Several strategies have been adopted in remediating HMs contaminated soil, but these techniques are very expensive and affect the physio-chemical properties of the soil. In contrast, the use of plants for remediation purposes known as phytoremediation found its application in the removal of contaminants in soil. In this method, the plant absorbs these metals from the soil thereby reducing the concentration of the metals in the contaminated soil. Phytoremediation is classified as a green technology due to its ability to remove contaminants without introducing any secondary pollutants. The concept of phytoremediation in cleaning up contaminated soils is straightforward. Phytoremediation should be embraced as it does not require special skills for environmental sustainability. The review focuses on the strategies for remediation of toxic HMs from contaminated soils for environmental sustainability using the green plant.